El miedo al desorden: estrategias de recuperación del equilibrio social en el mito iliádico - Montes Miralles, Mª Yolanda (Gerión. Revista de Historia Antigua, 2006)
The following pages deal with those strategies aimed at the recovery of social order in iliadic myth. According to my opinion, the above mentioned strategies are a part of an “isos allos exclusive language” (“the same other”, that is to say, heroes/aristocrats), and help us to understand the ideal working of a society that is not a real one but an ideological one, which would be useful for the definition of a concrete group in a specific historical period.